Psychology of Communication : course of lectures. Lecture 5. Topic: Contacts with patient: Providing information and making decisions. Communication with personnel. Topic 8-9 - Луценко, Олена Львівна; Lutsenko, O. L. (Харків : Харківський національний університет імені В.Н. Каразіна, 2018)
Topic 8. Contacts with patient: Providing information and making decisions: Providing information related to the working diagnosis. Providing information on next steps. Making decisions. Elicited the patient’s perspective on the diagnosis and next steps. The phenomenon of compliance. Type of compliance. Finalizing plans for the next steps. Supporting emotions. Facilitating the expression of an implied or stated emotion. Effects of self-affirmation. Consequences of specific physician behaviors on certain patient outcomes. Topic 9. Communication with personnel (health-care teams): Staff relations. Benefits of group work. What kind of challenges does group work bring and how to deal with them. Size of groups, time of work, roles, strategies. The best techniques of group work. Comparison of team and individual work. The effectiveness of the teams. Composition of teams.
Keywords: communication; psychology; medical; healh care